Practical Applications of Computational Biology and Bioinformatics, 12th International Conference - Fdez-Riverola, Florentino; Mohamad, Mohd Saberi; Rocha, Miguel; De Paz, Juan F.; González, Pascual; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces the latest international research in the fields of bioinformatics and computational biology. It includes various studies in the area of machine learning in bioinformatics, systems biology, omics data analysis and mining, biomedical applications and sequences, which were selected by an international committee and presented at the 12th International Conference on Practical Applications of Computational Biology & Bioinformatics held in Toledo in June 2018.
Keywords: Computational intelligence; Artificial intelligence; Bioinformatics; Computational Intelligence; Artificial Intelligence; Bioinformatics